Hope as a Mediator between Optimism and Grit among Adolescents who Study in Boarding Schools - Rahman Pranovri Putra; Farida Agus Setiawati; Auliya Ramadhanti (Journal An-Nafs: Kajian Penelitian Psikologi, 2024)
Hope is important in mediating the relationship between optimism and grit in adolescents. Optimism, believing in positive future outcomes, can promote constructive attitudes. However, hope helps to direct such optimism into concrete actions in the form of grit in achieving goals. This study examined the effect of optimism on grit, with hope as a mediating among adolescents in Islamic boarding schools. This study used a quantitative, ex-post facto approach involving 367 adolescents selected through multistage random sampling. Data were collected using the Short Grit Scale (Grit-S), Optimism Scale, and Adult Dispositional Hope Scale. Data was analyzed using multiple regression with Process v4.2 macro of Hayes Model 4 through SPSS. The findings showed a significant positive influence between optimism and grit through hope, with complete mediation. Therefore, it is crucial for boarding schools to foster optimism and set realistic goals, as this can improve students' fortitude and academic achievement. The practical implications of these findings are that teachers and Islamic boarding school administrators can teach and promote an optimistic attitude and realistic and positive goal setting, reward small achievements, and goal visualization exercises can help increase adolescent hope and grit.